China's changing trade pattern - Ren, Li (2009)
In recent years, the rapid expansion of China’s trade surplus has been a key development in the global economy. According to China’s customs statistics, the trade surplus amounted to a mere 32 billion US dollars in 2004. However, since 2005 the trade surplus has ballooned, and it reached nearly 180 billion US dollars in 2006, or close to 7% of China’s GDP. The surplus has also been debated as it is unsure that what caused it. Some argue that the huge amount of trade surplus is a clear sign of undervalued renminbi and unfair price competitiveness. While others have viewed that it reflected changes in China’s economic structure and associated shifts in its role within regional and global production chains. This study tries to find some in-depth structure of China’s export and import by estimating export and import with equations in order to have some insight of the trade surplus. Price elasticity and demand elasticity of export and import are of our particular interests, as well as the changing pattern of China’s trade.